IMPROVING STUDENTS' SKILL IN WRITING RECOUNT TEXTS THROUGH PICTURE SERIES - Yunita, Ita; Regina, Regina; Rezeki, Yanti Sri (TELL - US JOURNAL, 2024)
This research aimed to describe how picture series improved students’ skill in writing recount text. This research was conducted to Year-8 students of SMPN 01 Semparuk in Academic Year 2023/2024. The students in class VIII B that consist of 23 students were the subject of this research. The method used in this research was Classroom Action Research which has been conducted in two cycles. The researcher used observation checklist table, field notes and writing test as the tools of data collection in this research, and the data has been analyzed both qualitatively and quantitatively by referring to the result of tools of data collection. The finding showed that the use of picture series improved students’ skill in writing recount text. Students’ participation, students’ mastery of writing recount text, students’ writing test score and class situation had a better improvement from the first cycle to the second cycle. It could be concluded that students’ skill in writing recount text through picture series improved.